Pengaruh Penerapan Good Corporate Govermance Terhadap Kinerja Keuangan Pada Koperasi Pemasaran Trangsan Manunggal Jaya Kabupaten Sukoharjo - Rindi Novitasari; Djoko Kristianto (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) principles on the financial performance of Koperasi Pemasaran Trangsan Manunggal Jaya, including transparency, accountability, responsibility, independence, and fairness. Data were collected through questionnaires, observations, and literature studies involving 46 respondents knowledgeable about GCG implementation within the cooperative. The data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that transparency, accountability, and responsibility have a significant effect on financial performance, while independence and fairness do not. The regression model is statistically significant, with an R² value of 0.549, indicating that the independent variables explain 52.8% of the variation in financial performance, while the remaining 47.2% is influenced by other factors outside the model, such as work environment, company size, market competition, operational costs, and working capital